Analisis Hukum Pidana Atas Keamanan Data Dan Serangan Siber Terhadap Pertahanan Nasional: Criminal Law Analysis of Data Security and Cyber ​​Attacks on National Defense - Hasrina, Sri; Sari, Inda; Manguma, Thiara Tri Funny; Fatra, Emil (KIRANA : Social Science Journal, 2025)
As digital technology advances, cyber threats are becoming increasingly complex and have a significant impact on national security. Cyber ​​attacks, including data theft, system destruction, and takeover of critical infrastructure, pose new challenges in maintaining national stability. In the context of criminal law, handling cyber attacks requires regulations that are able to answer the challenges of this high-tech threat, both in terms of prevention and enforcement. This study aims to identify aspects of criminal law that are relevant in protecting data security and analyze the existing legal framework, including the effectiveness, weaknesses, and potential for legal development in responding to cyber threats. Through a normative approach, this study also evaluates efforts to protect critical data and infrastructure, by looking at comparisons from several other countries. The results of this study are expected to contribute to the formulation of more comprehensive criminal law policies to protect national interests from cyber threats.